Life cycle risks and the politics of the welfare state - Jensen, Carsten (Aarhus University Press, 2019)
Life Cycle Risks and the Politics of the Welfare State' presents the dual risk model of the welfare state. Previous research in the field has predominantly studied the role of modernization and the associated labor market risks; this book gives equal weight to a different class of social risks, namely those related to the life cycle. Labor market and life cycle risks each have profound, but distinct consequences for the political process of the welfare state, including public opinion formation, party competition, and public policy-making. The dual risk model helps us to understand why some social programs are prioritized over others in terms of political attention and public spending - and how this prioritization leads to mounting economic inequalities in modern-day societies.